2021
DOI: 10.3389/fnins.2021.610957
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Binaural Hearing in Adults: A Selected Review of the Literature

Abstract: Despite over 100 years of study, there are still many fundamental questions about binaural hearing that remain unanswered, including how impairments of binaural function are related to the mechanisms of binaural hearing. This review focuses on a number of studies that are fundamental to understanding what is known about the effects of peripheral hearing loss, aging, traumatic brain injury, strokes, brain tumors, and multiple sclerosis (MS) on binaural function. The literature reviewed makes clear that while ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 120 publications
(233 reference statements)
0
19
0
1
Order By: Relevance
“…The role of the diotic FM detection task in predicting SEP and SRM are both consistent with the results of Strelcyk and Dau [ 75 ] who also demonstrated that TFS sensitivity was related to speech understanding in a binaural listening task. Such a relationship may be related to the need for very precise timing at the level of the cochlear nucleus for the extraction of binaural cues [ 76 ] that lead to improved speech understanding in the presence of spatially distributed sound sources. It is surprising, however, that the diotic FM task was a stronger predictor of spatial abilities than was the dichotic task, which actually involves a binaural judgment.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the diotic FM detection task in predicting SEP and SRM are both consistent with the results of Strelcyk and Dau [ 75 ] who also demonstrated that TFS sensitivity was related to speech understanding in a binaural listening task. Such a relationship may be related to the need for very precise timing at the level of the cochlear nucleus for the extraction of binaural cues [ 76 ] that lead to improved speech understanding in the presence of spatially distributed sound sources. It is surprising, however, that the diotic FM task was a stronger predictor of spatial abilities than was the dichotic task, which actually involves a binaural judgment.…”
Section: Discussionmentioning
confidence: 99%
“…With two ears, humans and animals can immediately determine the location of noise produced by something without having to adjust their heads ( Lynne et al, 2012 ; Micheal et al, 2018 ). Binaural hearing benefits spatial perception, auditory scene analysis and listening comprehension ( He et al, 2017 ; Snapp and Ausili, 2020 ; Gallun, 2021 ). The auditory ascending system has many hierarchical partitions of nuclei in the mammalian brain from the cochlear nuclei (CN) to the auditory cortex ( Winer and Schreiner, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Aging is associated with changes in visual and auditory pathways from eyes and ears to cortical areas ( Andersen, 2012 ; Recanzone, 2018 ). Regarding auditory localization, older adults reportedly show reduced accuracy and precision even with age-adjusted normal hearing thresholds ( Dobreva et al, 2011 , 2012 ; Freigang et al, 2014 , 2015 ), possibly due to age-related deficits in processing interaural temporal difference, interaural level difference, and monaural spectral cues that are crucial for sound localization (for a review, see Gallun, 2021 ). Older individuals also show impaired visual spatial abilities despite normal vision, such as reduced accuracy and precision in spatial updating ( Bennett et al, 2017 ) and impaired scene perception which requires integration of global spatial information ( Meng et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%